Narratives of Renewable Energy in Rural Alberta: Exploring the (In)Visibility of New Infrastructures - Bettini, Anna (Anthropologica)

(untitled) (University of Victoria, 2025)
Over the years, Alberta has seen a rapid growth in the construction and expansion of renewable energy infrastructure, particularly in solar and wind energy projects. This transition promises to bring new financial advantages such as lease payments, property taxes, and community support to smaller rural localities. However, they also come with challenges. Large-scale projects, often built by foreign companies, reshape familiar landscapes with transmission lines, steel towers, and fields of solar panels. The visibility of these initiatives significantly influences local perceptions, as large wind farms and solar installations often face scrutiny from residents. Concerns about aesthetics, land use, and potential impacts on agriculture lead to resistance among communities who feel their livelihoods are threatened. The hidden nature of fossil fuel infrastructures masks significant power dynamics and long-term costs of relying on oil and gas..This paper explores how people in rural Alberta interpret and respond to these visible changes in their surroundings. Drawing on ethnographic research, it examines the tensions and possibilities that emerge when renewable energy goals intersect with questions of place and justice. By listening to diverse voices and experiences, the paper puts in the foreground the social dimension of the energy transition. Understanding this dimension is crucial in navigating the obstacles and injustices encountered as we move forward.